Effect of Fermentation of Palm Kernel Meal by a Bacterial and Yeast Consortium on Nutritional Quality - Fajri Maulana; Satri Yusasra Agasi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Palm kernel meal is a potential alternative feed ingredient due to its abundant availability; however, its utilization in poultry diets is limited by suboptimal nutritional quality. One strategy to improve its nutritional value is fermentation using microorganisms. This study aimed to evaluate the effect of palm kernel meal fermentation by a bacterial and yeast consortium on its nutritional quality. The experiment was conducted using a completely randomized design with four treatments and five replication: a (unfermented palm kernel meal), B (fermentation with Bacillus subtilis), C (fermentation with Saccharomyces cerevisiae), and D (combined fermentation with Bacillus subtilis and Saccharomyces cerevisiae). The observed parameters included moisture content, metabolizable energy, organic matter, and inorganic matter. Data were analyzed using analysis of variance (ANOVA) at a 95% confidence level. The results showed that fermentation using the bacterial and yeast consortium significantly affected (P<0.05) moisture content and metabolizable energy, but had no significant effect (P>0.05) on organic and inorganic matter. The combined treatment produced the best values, with a moisture content of 12.25%, a metabolizable energy of 3139.52 kcal/kg, an organic matter of 95.57%, and an inorganic matter of 4.43%. This study concludes that the fermentation of palm kernel meal using a consortium of Bacillus subtilis and Saccharomyces cerevisia is the most effective treatment for improving nutritional quality, particularly by increasing metabolic energy without reducing the content of organic and inorganic compounds.